2002
DOI: 10.1079/bjn/2002552
|View full text |Cite
|
Sign up to set email alerts
|

Pet food and feed applications of inulin, oligofructose and other oligosaccharides

Abstract: Prebiotics may be considered as functional food ingredients. They are attracting considerable interest from pet owners, pet food manufacturers, livestock producers and feed manufacturers. The most common forms of prebiotics are nondigestible oligosaccharides (NDO), including inulin, oligofructose mannanoligosaccharides, gluco-oligosaccharides, and galacto-oligosaccharides. These NDO are nondigestible by enzymes present in the mammalian small intestine, but are fermented by bacteria present in the hindgut of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 16 publications
(15 reference statements)
1
33
0
2
Order By: Relevance
“…The results of the current study have shown that feeding orally just 3% of Jerusalem artichoke powder did not sensibly alter microbiota in GIT of pigs in comparison with other trial groups. It is established, that oligosaccharides incorporated in swine diets at levels ranging from 5 to 40 g/kg per diet have resulted in a variet, but generally not significant, effect regarding beneficial modulation of microbial populations detected in feces of swine (Mikkelsen et al 2003) and the supplementation of piglets a diet with 40 g FOS/kg had no effect on anaerobic bacteria and enterobacteria in feces of pigs (Flickinger and Fahey 2002). As to numbers of E.coli, no differences were detected altogether (Tako et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The results of the current study have shown that feeding orally just 3% of Jerusalem artichoke powder did not sensibly alter microbiota in GIT of pigs in comparison with other trial groups. It is established, that oligosaccharides incorporated in swine diets at levels ranging from 5 to 40 g/kg per diet have resulted in a variet, but generally not significant, effect regarding beneficial modulation of microbial populations detected in feces of swine (Mikkelsen et al 2003) and the supplementation of piglets a diet with 40 g FOS/kg had no effect on anaerobic bacteria and enterobacteria in feces of pigs (Flickinger and Fahey 2002). As to numbers of E.coli, no differences were detected altogether (Tako et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…However, the effects on hepatic lipid metabolism are worth further study. There is also great interest in prebiotics in the pet food and animal feed industry (Flickinger and Fahey, 2002), where improved control of gastrointestinal infection is reported and enhanced growth performance is seen in poultry especially. Other areas of interest include prebiotics and immunomodulation and the gut immune system, glycaemic control, behavioural effects, especially cognitive performance, and the enhancement of probiotic activity in synbiotics.…”
Section: Health Benefitsmentioning
confidence: 99%
“…As syrup and molasses are coloured materials and the FOS specifications for human 25 nutrition are very restrictive in this subject, the FOS obtained by the methods described in We are very grateful to Azucarera Ebro (Valladolid, Spain) for supplying beet sugar syrup 10 and molasses. We thank Drs.…”
mentioning
confidence: 99%
“…Effect of pH and substrate concentration on FOS production 25 The presence of a fructosyl-transfer activity in commercial Pectinex Ultra SP-L from…”
mentioning
confidence: 99%
See 1 more Smart Citation